EARLY DETECTION OF EPITHELIAL OVARIAN CANCER USING HE4, CA-125, AND ROMA SCORE: A SYSTEMATIC REVIEW (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Epithelial ovarian cancer is one of the most lethal gynecological malignancies because most patients are diagnosed at an advanced stage. Early detection remains a major clinical challenge. Cancer antigen 125 (CA-125) is widely used in ovarian cancer evaluation, but its diagnostic utility is limited by reduced specificity in benign gynecological conditions and reduced sensitivity in early-stage disease. Human epididymis protein 4 (HE4) and the Risk of Ovarian Malignancy Algorithm (ROMA), which combines HE4, CA-125, and menopausal status, have been proposed to improve diagnostic accuracy. Objective: To systematically evaluate the diagnostic performance of HE4, CA-125, and ROMA score in the early detection of epithelial ovarian cancer. Methods: A systematic review was conducted according to PRISMA 2020 guidelines. PubMed, Scopus, Web of Science, Embase, and Google Scholar were searched for diagnostic accuracy studies evaluating HE4, CA-125, and/or ROMA score in women with suspected epithelial ovarian cancer or adnexal masses. Studies reporting sensitivity, specificity, positive predictive value, negative predictive value, area under the curve, or sufficient data for diagnostic interpretation were included. Histopathology was considered the reference standard. Study quality was assessed using the QUADAS-2 tool. Results: A total of 642 records were identified. After removing 148 duplicates, 494 records were screened. Seventy-three full-text articles were assessed, and 28 studies involving 7,846 women were included. Of these, 2,318 women had epithelial ovarian cancer and 5,528 had benign ovarian or gynecological conditions. Early-stage epithelial ovarian cancer was reported in 1,014 cases. CA-125 showed pooled sensitivity of 82.4% and specificity of 74.2%. HE4 showed sensitivity of 78.6% and higher specificity of 88.9%. ROMA score demonstrated the best overall diagnostic balance, with pooled sensitivity of 87.1%, specificity of 84.7%, and area under the curve of 0.92. In early-stage disease, ROMA showed sensitivity of 76.5%, compared with 70.9% for HE4 and 66.8% for CA-125. Conclusion: HE4 and ROMA score improve diagnostic specificity and overall accuracy compared with CA-125 alone. ROMA score appears particularly useful for risk stratification in women with adnexal masses. However, none of the biomarkers alone is sufficiently accurate for population-level screening. Combined use of serum biomarkers, imaging, menopausal status, and clinical assessment may improve early detection of epithelial ovarian cancer.